(untitled) (Sains Humanika, 2021)
This study aimed to examine the relationship between the brand personality and the intention to buy counterfeit luxury branded products among University ‘X’ students. Researchers have used the Brand Personality Scale introduced by Aaker (1997) to measure brand personality. Meanwhile, the Attitude Survey, Buy Genuine Luxury Fashion Products or Counterfeits introduced by Yoo and Lee (2009) was used to measure the buying intention of counterfeit luxury branded products. This study involved 118 respondents from University ‘X’ students. The data collected was analyzed using Statistical Package for Social Science (SPSS) version 20. The findings showed that there is no significant relationship between the brand personality and the intention to buy counterfiet luxury branded products among University ‘X’ students.